STRATEGI BISNIS COFFEE SHOP PASCA PANDEMI COVID-19 (STUDI PADA ADIKSI COFFEE PURNAWIRAWAN DI BANDAR LAMPUNG) - Damayanti, Riska Alisia; Sugiono, Arif; Nugeraha, Prasetya (Jurnal Kompetitif Bisnis, 2023)
After the Covid-19 pandemic, many business actors, one of which was a coffee shop, went bankrupt due to the outbreak. The coffee shop business which is quite well-known in Bandar Lampung, namely Adiksi Coffee. In the midst of the booming coffee shops experiencing bankruptcy, Adiksi Coffee opened a new branch, so this study aims to explain the corporate strategy as well as the business and functional strategy implemented by Adiksi Coffee after the Covid-19 pandemic. This research was conducted using a descriptive method through a qualitative approach. The strategy for determining informants was by purposive sampling. The informants of this study were the managers and employees of Addiction Coffee. Based on the results of the study, it can be described that Adiksi Coffee in maintaining its business uses a corporate strategy as well as a business strategy, namely a growth strategy by carrying out market penetration and market development and the functional strategy used is a marketing strategy by carrying out a promotion strategy, an operating strategy by carrying out differentiation or differentiating , and human resource strategy by implementing company SOPs.